2021
DOI: 10.1186/s13047-021-00492-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and satisfaction of a mandatory continuing professional development programme amongst Aotearoa New Zealand podiatrists

Abstract: Background Aotearoa New Zealand (NZ) registered podiatrists are required to participate in a mandatory continuing professional development (CPD) programme. This study investigated podiatrist’s perceptions and satisfaction surrounding mandatory CPD requirements following the implementation of a new 2-year CPD programme. Methods A cross-sectional study of NZ registered podiatrists was conducted between October 9th and December 9th, 2020. Data was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The overarching message was improvements across several parameters could be made, including frequency, content, relevance, accessibility, and delivery, with respondents suggesting solutions for many of the concerns raised. The results of the current study support previous international findings that CPD is perceived to be beneficial by clinicians [ 20 , 28 , 40 45 ]. There were also similarities shared between our study and those reported elsewhere for frustrations with scarcity of specialised content, cost and available funding, time commitment required, and the lack of national infrastructure to support quality CPD [ 8 , 20 , 27 , 28 , 32 , 40 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The overarching message was improvements across several parameters could be made, including frequency, content, relevance, accessibility, and delivery, with respondents suggesting solutions for many of the concerns raised. The results of the current study support previous international findings that CPD is perceived to be beneficial by clinicians [ 20 , 28 , 40 45 ]. There were also similarities shared between our study and those reported elsewhere for frustrations with scarcity of specialised content, cost and available funding, time commitment required, and the lack of national infrastructure to support quality CPD [ 8 , 20 , 27 , 28 , 32 , 40 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study support previous international findings that CPD is perceived to be beneficial by clinicians [ 20 , 28 , 40 45 ]. There were also similarities shared between our study and those reported elsewhere for frustrations with scarcity of specialised content, cost and available funding, time commitment required, and the lack of national infrastructure to support quality CPD [ 8 , 20 , 27 , 28 , 32 , 40 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mandatory CPD programs most commonly focus on hours completed and do not assess the content, nor quality of the activity undertaken. Several gaps in the CPD system are documented in the literature and range from an emphasis on a time-based approach over quality and a lack of focus of translation to practice of learnings, to disincentives to engage in multidisciplinary learning and team building activities (Carroll et al, 2021;Fletcher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%